Efektivitas Prinsip Dan Implementasi Islami Pendidikan Karakter di Keluarga - Afandi, Moh. Hasyim; Kartikasari, Galuh (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Education is the key in forming the character of children early on, because the essence of education is not just limited to transfer of knowledge but also to transfer of values, all of those are done to build the character of the nations noble personality and cope with juvenile delinquency from various social deviations. Character education has been the National Action Plan since May 2nd, 2010 by Muh. Nuh as Education Minister of Indonesia. The draft sets the year 2010-2014 as consolidation and the placement of the foundation. Then in 2015-2019 as a consolidation strategy implementation and continued in 2020-2024 as a sustainable development. There are many factors that cause the importance of Indonesian society to work together to succeed the character education in Indonesia. Schools have a strategic role in value education, the reality shows that schools cannot do it alone. Apparently, the family has a big enough role. Family is the first moral educator for children. Their parents were the first moral teachers and directly influential element. Whereas, teachers at school can change at any time. Parent-child relationships are built upon a very meaningful emotional foundation that allows a child to feel loved and valuable or unloved and worthless. If the individual character is based on religious values as the foundation/main base, then will be born the soul of strong character and become strong nation shoots anyway. The main goal of character education according to Islam is to form the personality of learners so having ethics, and a good sense of culture and make it happen in everyday life.